DAMPAK PEMBERIAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. HOME KREDIT PEKANBARU - Irawan, Dika; Hidayat, Novit (Komunitas Manajemen Kompetitif, 2024)
This research aims to determine the effect of motivation on the performance of PT employees. Home credit PekanbaruThe research method we carried out was an associative method using a quantitative approach. The sample for this research was employees of PT. Pekanbaru Home Credit, totaling 66 employees using saturated sampling techniques, data collection using questionnaires while data analysis using multiple regression The research results found that work motivation had a significant effect on employee performance at PT.Home Kredit Pekanbaru